Antibacterial activity of cream, ointment, and emulgel of Ocimum basilicum L. essential oil against Propionibacterium acnes - Iramie Duma Kencana Irianto; Ismiyati Ismiyati; Enggar Witaningrum; Elly Nur Ayuningtyas; Meilana Maria Ulfah; Purwanto Purwanto (Majalah Obat Tradisional, 2023)
Propionibacterium acnes is bacteria that is commonly found on healthy human skin. However, unbalanced hormonal conditions can lead to excessive growth of P. acnes, a bacteria causing acne. Previous research reported that Ocimum basilicum L. essential oil (BEO) has activity against P. acnes. Therefore, this study aims to make BEO into cream, ointment, and emulgel forms to determine its properties and antibacterial activity on those topical drug delivery systems. The preparations consisted of variations in BEO concentrations of 5%; 10%; and 15%. The three preparations were evaluated based on organoleptic, homogeneity, pH value, adhesion, and spreadability. The antibacterial activity test of the three preparations against P. acnes was carried out by the good diffusion method with the observation of the diameter of the inhibition zone (in mm). The produced cream, ointment, and cream had a typical BEO aroma, yellowish white color, and homogeneous. Based on organoleptic consistency, the texture of the thicker and longer adhesion was ointment > emulgel > cream, respectively. The pH value of the topical preparation was 5-6 and easily leveled. Antibacterial activity against P. acnes from the strongest was ointment > cream > emulgel, with a value of 14,30 + 0,30 mm; 10,54 + 0,01 mm; 3,90 + 0,04 mm, respectively.